Innovative Computer Technologies for Estimating the Level of Economy Safety: Evolution, Current State and Prospects - Kostiuk, Tetiana; Olali, Nataliia; Martynenkov, Vadym; Kostiuk, Serhii (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article provides a system analysis of trends in the IT field of the global computer industry that changed the socio-economic conditions of everyday living. In particular, we describe such innovative software as Deductor Studio, Statistics, MS Exel, SPSS, Statgraphics, MapInfo, Mathcad, MatLab, Analyst, Model Economic Equilibrium and Automated Information Systems that are necessary for the implementation of production and circulation in the Enterprise Resource Planning(ERP), which has made it possible to show significant benefits of Statistics10 in the economy. We have scientifically proven that in the next 10 years, there will be a new perspective towards developing a system which will be based on software system Statistics, innovative technologies for complex service of e-commerce, which will be one of the main types of business in the development of a global network protocols of electronic data interchange, electronic auctions etc.
Keywords: evolution; innovative technology; software system; development strategy; strategic priorities; economy safety